(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Non-Hodgkin lymphoma (NHL) represents a heterogenous group of malignant lymphoproliferative neoplasms originating from lymphoid tissue cells and having distinct clinical, cytomorphological, immunological and molecular and genetic features. Primary orbital lymphomas are rare and account for approximately 1% of all NHL. Lymphomas are, however, the most common primary orbital tumor in adults 60 years of age and older. Purpose: To present a rare case of primary B-cell MALT lymphoma of marginal zone of the upper eyelid, to highlight its clinical features, and to demonstrate the importance of a multidisciplinary approach to its treatment. Results: A male patient presented to the eye clinic complaining of bilateral pterygium and periodic nasal congestion. Within the course of examination and prolonged observation, the ophthalmologist suspected the symptoms of massive orbital disease, and the patient was referred for magnetic resonance imaging (MRI) of the brain. On the basis of imaging assessment and the oncologist’s opinion, the patient was hospitalized at the Podillia Regional Oncology Center with a preliminary diagnosis of orbital lymphoma. Thereat, a final diagnosis of “extranodal, non-Hodgkin’s B-cell lymphoma of the marginal zone (MALT lymphoma) of Stage 3a, with metastases in the lungs, pleura and lymph nodes of the mediastinum” was established. At the moment, he is under observation by an oncologist and on the way to stabilization of his major disease. Conclusion: Management of orbital non-Hodgkin’s lymphomas remains a challenge requiring a multidisciplinary approach involving ophthalmologists and oncologists.